Coordination of technological complex (tc) subsystems of sugar mill considering the doubtful information - Shumyhay, Dmitry; Boyko, Regina (My University, 2012)
The paper considers an approach to setting the extended task of the coordination in technological complex of continuous type. In particular technological complex of the sugar mill is considered. The main features of the solution of the coordination problem are described.
Keywords: принципи координації; принципы координации; principles of coordination; підсистеми технологічного комплексу; нечіткі знання; часові ряди; функція мети; подсистемы технологического комплекса; нечеткие знания; временные ряды; функция цели; subsystem of technological complex; fuzzy knowledge; time series; function purpose; кафедра автоматизації та комп'ютерних технологій систем управління ім. проф. А.П. Ладанюка; кафедра інформаційних технологій, штучного інтелекту і кібербезпеки